Behaviour of physicochemical properties of foam mat dried acerola powder during drying processing and storage - Diep Ngoc Thi Duong; Nhi Tuyet Thi Nguyen; Binh Quang Hoang (Vietnam Journal of Science, Technology and Engineering, 2025)
Acerola is a rich source of vitamin C. However, the fruit is highly perishable after harvest. One widely adopted technique for extending the shelf life of fresh fruit and producing new products is dehydration. This study aimed to investigate the effects of drying temperatures (55, 65, and 75°C) and storage conditions (e.g., relative humidity and temperature) on the characteristics (moisture content, polyphenols, vitamin C) of acerola powder. The results indicated that a drying temperature of 75°C produced powder with the highest solubility (75.89%), vitamin C content (2571.56 mg/100 g dry matter (DM)), and total phenolic content (2245.36 mg GAE/100 g DM). The sorption isotherm curve of the acerola powder was described by the equation y=3.4687e0.0244x . Moreover, under all storage conditions (e.g., 4-6°C and room temperature), the powder’s water activity did not exceed 0.6. The degradation of vitamin C and polyphenols during storage followed the Arrhenius equation and first-order kinetics. These attributes exhibited z-values of 208.33 and 48.54°C, respectively, with activation energies of 8.03 and 34.71 kJ/mol. Low storage temperatures effectively mitigated the loss of vitamin C and polyphenols. The findings suggest that acerola powder can serve as a valuable supplement to enhance food products with bioactive compounds.